Macrocydia divergens, a new genus and species of Grapholitini (Lepidoptera: Tortricidae: Olethreutinae) from Central America - Brown, John W.; Baixeras, Joaquin (Zootaxa, 2006)
Macrocydia divergens Brown and Baixeras, new genus and new species, from Costa Rica and Panama, is described and illustrated. The new genus can be distinguished from other Grapholitini by its remarkably large size, distinctive pale forewing pattern, and elongate, porrect labial palpi. Other interesting morphological features of diagnostic value include female frenulum with two bristles (three in most Tortricidae), female genitalia with a single large signum (paired in most Grapholitini), and a well-defined chorda and M-stem in the forewing venation. Owing to its highly divergent appearance and the relatively unremarkable male and female genitalia of the single included species, which are similar to many species of Cydia and Grapholita, it is not possible to identify the closest relative of Macrocydia.